2022
DOI: 10.1111/geoj.12488
|View full text |Cite
|
Sign up to set email alerts
|

Daily water‐level forecasting for multiple polish lakes using multiple data‐driven models

Abstract: Water level in lakes fluctuates frequently due to the impact of natural and anthropogenic forcing. Frequent fluctuations of water level will impact lake ecosystems, and it is thus of great significance to have a good knowledge of water-level dynamics in lakes. However, forecasting daily water-level fluctuation in lake systems remains a tough task due to its non-linearity and complexity. In this study, two deep data-driven models, including gated recurrent unit (GRU) and long short-term memory (LSTM), were coup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 76 publications
1
1
0
Order By: Relevance
“…[35]. To confirm the results of this paper, Zhu et al studied 69 lakes in Poland for 30 day ahead water level prediction and concluded that the recurrent DL models performed similarly to attention-based recurrent DL models in terms of predictive performance [60]. The results of the LSTM algorithm between its variants, namely the Stacked LSTM and the Bidirectional LSTM, in the present study show that there is no significant difference in predicting less than 30 days ahead.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…[35]. To confirm the results of this paper, Zhu et al studied 69 lakes in Poland for 30 day ahead water level prediction and concluded that the recurrent DL models performed similarly to attention-based recurrent DL models in terms of predictive performance [60]. The results of the LSTM algorithm between its variants, namely the Stacked LSTM and the Bidirectional LSTM, in the present study show that there is no significant difference in predicting less than 30 days ahead.…”
Section: Discussionsupporting
confidence: 78%
“…In the future, the performance improvement over the Naïve Benchmark can be tested with other novel models, such as attention-based algorithms or other derivatives. However, the recent attempt to use an attention-based algorithm showed that it did not perform better than a recurrent network [60].…”
Section: Discussionmentioning
confidence: 99%